Oxford reading tree phonics: fun at school - Hunt, Roderick; Hepplewhite, Debbie Ruttle, Kate Brychta, Alex (Oxford University Press China, 2011)
A reader for children about the sounds that can be heard at the park and fairground. Includes reading notes for parents and teachers